Mitigation of liquation cracking in selective laser melted Inconel 718 through optimization of layer thickness and laser energy density - Luu, Duy Nghia (2022)
Conventionally, the main goal of process optimization in selective laser melting is to achieve the highest relative density. However, for Inconel 718, this study has demonstrated that the highest relative density does not correspond to the best mechanical properties. Moreover, similar relative densities can result in significant differences in mechanical properties. This phenomenon arises from the presence of cracks in the microstructures. The research was carried out to study the problem systematically using combinations of 2 layer thicknesses (40 and 50 μm) and 2 laser energy densities (3.17 and 3.47 J/mm2). Microcracks were observed near the melt pool boundaries and within the heat-affected zones of the newly deposited layer, occurring along the grain boundaries and interdendritic regions. Evidence was obtained to show that the cracking was associated with remelting of Laves phase; therefore, it was identified as liquation cracking. It is interesting to observe that layer thickness has a much greater influence on crack formation than laser energy density, owing to the significant change in the melt pool shape and grain boundary morphology when the layer thickness was changed. The influence of laser energy density was only observed at the larger layer thickness as the severity of cracking was amplified when laser energy density was increased due to microstructural coarsening. Thus, this presents a unique problem in additive manufacturing (AM) regarding liquation cracking in Inconel 718 as one of the key differences from conventional manufacturing is the successive heating and reheating of multiple layers of material in AM.